Pragmatic Goal in Context (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In traditional pragma linguistics, the main focus is on the speaker's communicative goal, and the listener's participation in meaning-content formation is not given much importance.Speech creativity and context are interrelated phenomena. It also mentions the need for context elements to be mutually adapted in the process of communication.